Clinical and microbiological analysis of mechanical and chemomechanical methods of caries removal in deciduous teeth - Moimaz, Suzely Adas Saliba [UNESP]; Okamura, Audrey Quintella Coelho [UNESP]; Lima, Daniela Coêlho; Saliba, Tânia Adas [UNESP]; Saliba, Nemre Adas [UNESP] (My University, 2019)
Purpose: This study evaluated carious tissue removal by mechanical and chemomechanical methods (Carisolv and Papacárie) through colony-forming unit (CFU) counts of Streptococcus mutans and Lactobacillus sp. Treatment acceptability, presence and level of pain, use of anesthesia, time required for caries removal and pain 24 h after treatment were also compared. Materials and Methods: A clinical trial with 32 individuals who had at least two deciduous molars with active occlusal caries lesions were selected and randomly divided into two groups (I and II). One lesion in each individual was excavated with hand excavator only. The remaining lesions were excavated using modified hand excavation and Carisolv in group 1 or modified hand-excavation and Papacárie in group 2. Bacterial samples were taken from each caries lesion before and after treatment. Results: All the methods reduced the amount of cultivable Streptococcus mutans and Lactobacillus sp. after treatment (p < 0.05) and no statistically significant difference was found between the groups (p > 0.05). There was 97% acceptability of treatments, and anesthesia was used in 14% of teeth. Pain was present 24 h after treatment in 6% of teeth. The mean times for caries removal by the mechanical and chemomechanical treatments were not statistically significantly different (p > 0.05). Conclusions: All treatments were found to effectively reduce bacterial counts (p < 0.05). There were no statistically significant differences (p > 0.05) among treatments or between clinical variables (p > 0.05).
Keywords: Deciduous teeth; Dental atraumatic restorative treatment; Dental caries; Pain; Papain